Bright expression of CD91 identifies highly activated human dendritic cells that can be expanded by defensins. Issue 4 (April 2015) - Cappelletti, Monica; Presicce, Pietro; Calcaterra, Francesca; Mavilio, Domenico; Della Bella, Silvia
Summary CD91 is a scavenger receptor expressed by different immune cells and its ligands defensins have been demonstrated to contribute to immune responses against infections and tumours. We previously demonstrated that CD91 is expressed on human monocyte‐derived dendritic cells (moDCs) and that human defensins stimulate in vitro the activation of these cells. In this study, we observed that CD91 is expressed at different levels on two distinct moDC subsets: CD91dim and CD91bright moDCs. Although CD91bright moDCs represented a small proportion of total moDCs, this subset showed higher levels of activation and maturation markers compared with CD91dim moDCs. The frequency of CD91bright moDCs increased by 50% after in vitro stimulation with recombinant human neutrophil peptide‐1 (rHNP‐1) and recombinant human β defensin‐1 (rHBD‐1), while lipopolysaccharide (LPS) stimulation decreased it by 35%. Both defensins up‐regulated moDC expression of CD80, CD40, CD83 and HLA‐DR, although to a lower extent compared with LPS. Notably, upon culture with rHNP‐1 and rHBD‐1, CD91bright moDCs maintained their higher activation/maturation status, whereas this was lost upon culture with LPS. Our findings suggest that defensins promote the differentiation into activated CD91bright DCs and may encourage the exploitation of the CD91/defensins axis as a novel therapeutic strategy to potentiate antimicrobial and anti‐tumour immune response.